Metabolic alkalosis in cystic fibrosis: from vascular volume depletion to impaired bicarbonate excretion - Soleimani, Manoocher (Frontiers in Endocrinology, 2024)
Cystic fibrosis (CF) is the most common life-threatening genetic disease in the United States and among people of European descent. Despite the widespread distribution of the cystic fibrosis transmembrane conductance regulator (CFTR) along kidney tubules, specific renal phenotypes attributable to CF have not been well documented. Recent studies have demonstrated the downregulation of the apical Cl -/HCO3 -exchanger pendrin (Slc26a4) in kidney B-intercalated cells of CF mouse models. These studies have shown that kidneys of both mice and humans with CF have an impaired ability to excrete excess HCO3 -, thus developing metabolic alkalosis when subjected to excess HCO3 -intake.The purpose of this minireview is to discuss the latest advances on the role of pendrin as a molecule with dual critical roles in acid base regulation and systemic vascular volume homeostasis, specifically in CF. Given the immense prevalence of vascular volume depletion, which is primarily precipitated via enhanced chloride loss through perspiration, we suggest that the dominant presentation of metabolic alkalosis in CF is due to the impaired function of pendrin, which plays a critical role in systemic vascular volume and acid base homeostasis.